Immunogenetic investigation of WAS patients revealing impaired IL-6/STAT3 signaling in T cells - Bouzakoura, Firas; Mekki, Najla; Ben Khaled, Monia; Maaloul, Ines; Ben Taieb, Aicha; Zammeli, Amal; Ben-Ali, Meriem; Tira, Mariem; Ben-Hammadi, Ansem; Kamoun, Thouraya; Ouederni, Monia; Barbouche, Mohamed-Ridha; et al. (Frontiers in Immunology, 2025)
Wiskott-Aldrich syndrome (WAS) is an inborn error of immunity caused by loss-of-function mutations in the WAS gene, which encodes WASp, a key regulator of cytoskeletal remodeling. In addition to microthrombocytopenia, affected individuals often present with recurrent infections, eczema, eosinophilia and elevated IgE levels, suggesting a potential pathophysiological overlap with STAT3 hyper-IgE syndrome (HIES). Given these shared features, we investigated the immunogenetic characteristics of three WAS patients and explored the IL-6/STAT3 pathway as a potential underlying mechanism. Flow cytometry revealed absent WASp expression in P1 and P3, while P2 showed reduced level. Genetic analysis identified three hemizygous mutations: A56V substitution within the WH1 domain in P1, and two splice site mutations, c.360 + 1G>T and c.734 + 1G>C, in P2 and P3, respectively. Interestingly, all WAS patients showed impaired STAT3 phosphorylation in T cells following IL-6 stimulation and SOCS3 induction was markedly decreased. These results further suggest a potential link between WASp and STAT3. Considering the interaction of WASp with DOCK8-WIP in lymphocytes and the critical role of DOCK8 in regulating STAT3 phosphorylation following IL-6 stimulation, we analyzed DOCK8 expression in lymphoblastoid cell lines. We demonstrated normal DOCK8 levels suggesting that STAT3 signaling defect is due to the absence of WASp rather than DOCK8 loss. Our results demonstrate the impairment of T cell IL-6/STAT3 pathway in WAS patients which could underlie, in part, the overlapping phenotype with HIES patients.